Is current rising trends of cesarean section –justified ? - Preetkamal, .; Kaur, Harmanpreet; Nagpal, Madhu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cesarean section has become more prevalent over the years due to various factors and is exceeding the tolerable limit specified by WHO. The objective of this study was to analyze cesarean section rates in our department and to identify the factors that contributed to rising cesarean section rate considering both institutional aspects as well as socioeconomic causes. Methods: It was a retrospective study conducted between May 2015 to April 2016 and included all pregnant patients booked in antenatal clinic and unbooked patients admitted in early labour in whom cesarean section was conducted later along with cases coming in emergency for which cesarean section was indicated. Data was collected and categorized on the basis of age, parity, socioeconomic status, education and according to Robson’s ten group classification. Results: The cesarean section rate was found to be 33.2% in our study. The most common indication was repeat cesarean section, fetal distress, and breech presentation. Robson’s group1 had maximum cesarean rates followed by group 5, 6 and 3. Conclusions: Tertiary care centers cannot be expected to have a similar rate as primary and secondary ones due to high number of complex cases referred to them. Though effort should be made to keep the cesarean rate at a low level as suggested by WHO but denying it for an indicated case just to adhere to keep low rate jeopardizes maternal and fetal health. Hence no definitive guidelines can be followed and a very judicious approach is needed.